Assessment The Effect of Heavy Metals on Autism Patients (Journal of the College of Basic Education, 2025)
This study aims to analyze the potential impact of heavy metals, such as lead, mercury, and cadmium, on patients with autism spectrum disorder. It provides a theoretical review of studies that have demonstrated the relationship between heavy metal accumulation and the behavioral and neurological effects of autism. This study relies on an analysis of data on exposure to these elements, such as food or pollution, and how they are measured to obtain the causes related to the autism spectrum disorder.